Application of electron spin resonance (ESR) dating to ductile shearing: Examples from the Qinling orogenic belt, China. (April 2016) - Ren, Shenglian; Song, Chuanzhong; Li, Jiahao
Abstract: Shear zones are common structures in orogenic belts and elucidation of the tectonic evolution of these orogenic belts to a large degree depends on understanding the kinematics and timing of shear deformation. However, there is a lack of an accurate, fast and convenient way to determine the timing of deformation. In this paper, we apply the ESR (electron spin-resonance spectroscopy) dating method to three syntectonic quartz veins from the Funiushan tectonic belt in the Qinling orogenic belt in central China. The results agree well with the available ages of deformation in the area obtained through other dating methods. This demonstrates the accuracy and feasibility of using the ESR method to date quartz crystals formed during deformation. The method is fast and convenient, and satisfies the accuracy requirement. It is an effective means for determining the timing of deformation, especially in areas with intensive fluid activity during deformation. Highlights: Quartz vein formed by ductile shearing can be used for ESR dating. The ESR signal turns to zero when temperature approach 400 °C. The total error of ESR dating is less than 10 percent of absolute age. It needs to consider influence of later tectonic event while do ESR dating.